A subset analysis of efficacy and safety outcomes from phase 3 clinical studies of ixekizumab for the treatment of patients with severe plaque psoriasis. (2nd January 2022) - Spelman, Lynda; Rubel, Diana; Brnabic, Alan; Burkhardt, Nicole; Riedl, Elisabeth; Foley, Peter
Abstract: Background: Factors beyond the Psoriasis Area and Severity Index (PASI) contribute to disease severity in psoriasis and potentially affect treatment responses. Objective: This subset analysis of data from two phase 3 clinical studies assessed baseline parameters in patients with different degrees of psoriasis severity in order to determine treatment responses to ixekizumab and safety outcomes. Methods: This study used integrated data from the UNCOVER-2 and -3 trials involving 2709 patients with chronic plaque psoriasis to assess the efficacy and safety of ixekizumab in three subgroups of patients, defined by PASI > 15 (group 1), PASI > 15 and history of ≥3 non-biologic systemic therapies (group 2), or PASI = 12-15 (group 3). Results: In groups 1 and 2, additional baseline features were identified that could influence treatment responses, including age at disease onset, Dermatology Life Quality Index, and work productivity. Irrespective of subgroup, ixekizumab demonstrated high PASI responses at weeks 12 and 60, which were evident as early as week 2. Adverse events did not differ across subgroups. Conclusion: Our data support the efficacy, early onset of action, and maintained response of ixekizumab as observed in previous trials, and highlight the complexity of comprehensively defining disease severity in psoriasis.